Substance use and shame: A systematic and meta-analytic review. (June 2019) - Luoma, Jason B.; Chwyl, Christina; Kaplan, Josh
Abstract: Shame has been hypothesized to both contribute to and protect against problematic substance use, yet no systematic reviews of these relationships exist. We identified 42 studies of the empirical associations between shame and substance use or substance use-related problems in order to elucidate this relationship. A meta-analysis of 14 samples found no significant association between shame and substance use ( r  = 0.00). A meta-analysis of 18 samples found a significant association between shame and substance use-related problems ( r  = 0.16), an effect size similar to that found in previous meta-analyses of the association between depression and substance use. Samples in treatment for substance use disorders had higher experienced shame than controls. Over longer periods of time (i.e., months to years) shame was not a reliable predictor of substance use. Over shorter periods of time (i.e., hours to days), shame predicted more substance use, though this was qualified by complex interaction effects with shame sometimes appearing to have protective functions. Two studies demonstrated that substance use in particular contexts results in shame. The discussion identifies potential moderators of the relationship between shame and substance use and recommendations future research directions. Highlights: Shame and substance use had no significant association across cross-sectional studies Shame was significantly associated with more substance use-related problems across cross-sectional studies Shame appears to be both an antecedent and consequence of substance use in certain contexts Within-subjects studies and studies identifying moderators of the association between shame and substance use are needed